An Experimental Research on Crack Propagation Regularity During Fracture Grouting. Issue 3 (February 2021) - Cheng, Shaozhen; Yang, Fa; Dai, Yuchen; Yang, Zili; Shi, Ye
Abstract: A new grouting model test device has been developed to model the fracture grouting process and improve understanding of the crack propagation regularity during grouting. It was concluded that the propagation process of crack is not one-time formed but undergoes the sequential mode of "expansion, stagnation, re-expansion, re-stagnation" after fracture initiation. The smaller the grouting pressure is, the longer the stagnation time is, and the smaller the crack propagation velocity is. The crack width increases rapidly when the crack tip stagnates or the expansion speed is small. Research results can help achieve better grouting aims and realize grouting safety in practice